The orchids of John Henry Lance (1793–1878) - Ossenbach, Carlos (Universidad de Costa Rica, 2020)
John Henry Lance, a British barrister, spent a ten-year term in Surinam as Judge appointed to the ‘Mixed Court’ in Paramaribo, a post created to supervise the compliance of the Dutch authorities with a treaty signed between the Netherlands and England in 1818 prohibiting the slave trade in the Dutch colonies. During his term in Paramaribo, Lance, a friend of Bateman and Lindley, collected several new orchid species. However, his collection of watercolors depicting plants from Surinam, many of them orchids, would appear to be more important. Some of these were painted by himself, others by the Surinamese artist Gerrit Schouten. The orchids of this collection, never published, were supplied by the Lindley Library of the R.H.S. and are reproduced here with its kind permission. Key Words: botanical illustration, history of botany, Orchidaceae, Surinam